Serum 8-OHdG levels correlate with endothelial dysfunction and carotid intima-media thickness in hemodialysis patients - YIN Xiao-wen; HAO Yu-jie; PEI Hua-ying; DONG Yan-fei; TIAN Li-ming; WANG Yun-hong (Linchuang shenzangbing zazhi)
Objective To determine the serum levels of 8-hydroxydeoxyguanosine(8-OHdG)、endothelin-1(ET-1)、 endothelial nitric oxide synthase(eNOS) and measuring carotid intima-media thickness(CIMT) in hemodialysis(HD) patients.Explore the relationshipbetween oxidative stress in endothelial dysfunction,atherosclerosis.Methods Fifty-two non-diabeticpatientstreated by hemodialysis for more than three months in the people’s Hospital of Oiarfan City Hebei provincefrom 2014.10 to2015.4,and forty-five healthy control group were included in the study.Serum 8-OHdG and ET-1 levels were quantified using enzyme-linked immunosorbent assay and radioimmunoassay respectively.The eNOS activities were measured by nitrate reductase assay.Carotid intimal-medial thickness(CIMT)was assessed by quantitative carotid artery ultrasonography.Results CIMT were significantly higher in HD patients compared with control group as[(l.31 ±0.29) mm 比(0.82 ± 0.21) mm,P<0.01].The incidence of atherosclerosis in HD patients was 78.85%.Serumlevels of 8-OHdG and ET-1 were increased in HD patientscompared with control group as[(38.30 + 9.34) ng/ml 比(7.24 + 0.87) ng/ml,P<0.01)].[(138.35 ±31.12) pg/ml 比(16.40 ± 1.21) pg/ml,P<0.01].The eNOS activities were significantly lower in HD patients compared with control group as[(12.67 ± 1.66) U/ml ft(14.05 ± 1.56) U/mh,P<0.01].Linear regression analysis showed that the levels of serum 8-OHdG had a significant positive correlation with serum ET-1 and CIMT(P<0.01),but a negative correlation with serum eNOS and Kt/V(P<0.01).In addition,the levels of serum 8-OHdG had significant positive correlations with dialysis duration,high sensitivity C-reactive protein(hs-CRP) and blood pressure(P<0.01).Conclusions The endothelial dysfunction in HD patients was significant and it was positive correlation with the oxidative stress.The oxidative stress was involved in the occurrence of endothelial dysfunction in HD patients.The levels of serum 8-OHdG could serve as an independently risk factors for atherosclerosis in HD patients.